2019
DOI: 10.3389/fimmu.2018.03095
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Natural Killer Cells in Gastric Cancer

Abstract: Gastric cancer (GC) is one of the most common cancers, with a high incidence of cancer death. Despite various therapeutic approaches, the cures and prognosis of advanced GC remain poor. Natural killer (NK) cells, which are known as important lymphocytes in innate immunity, play vital roles in suppressing GC initiation, progression, and metastases. A wide range of clinical settings shows that increasing the number of NK cells or improving NK cell antitumor activity is promising in GC patients. NK cell adoptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 105 publications
(116 reference statements)
0
53
0
Order By: Relevance
“…For example, autologous cell transplantation has been used in clinical settings, including boosting the immune system function for immunotherapy approaches. In particular, the auto-transplantation of ex vivocultivated NK cells has led to an improved outcome in various cancer situations [17][18][19][20] .…”
mentioning
confidence: 99%
“…For example, autologous cell transplantation has been used in clinical settings, including boosting the immune system function for immunotherapy approaches. In particular, the auto-transplantation of ex vivocultivated NK cells has led to an improved outcome in various cancer situations [17][18][19][20] .…”
mentioning
confidence: 99%
“…Additionally, NK cells express two inhibitory immune checkpoint receptors including lymphocyte activation gene 3 and T cell Ig mucin receptor 3 (also known as HAVCR2) . These receptors are under improvement as effective targets when combined with PD1 blockade, showing that NK cells antitumor functions can be revealed via new immunotherapy combinations, while NK cell adoptive therapy showed limited value because of the limited number of available NK cells …”
Section: Therapeutic Usage Of Ilcs In Cancer Treatmentmentioning
confidence: 99%
“…Several studies have shown the following effects of NK cells in different cancers: NK cells have been shown to be effective in patients with advanced lung cancer; Herceptintreated NK cells have been found to have therapeutic potential in the treatment of patients with human epidermal growth factor receptor 2 (Her2 + ) and Herceptin-intolerant breast cancer; expanded and cryopreserved NK cells are promising candidates for cellular immunotherapy in patients with pancreatic carcinoma; NK cells inhibit metastesis of ovarian carcinoma cells in murine models; CIK cells may become a novel therapeutic modality for rhabdomyosarcoma after allogeneic HSCT; CAR-engineered CIK cells may become valuable in the treatment of HR soft tissue sarcoma in children; and expanded and CIK cells are safe and well tolerated and they enhance cytotoxicity against gastric carcinoma [162,[265][266][267][268][269][270][271]. A meta-analysis, that included 29 clinical trials involving 2610 patients, has been shown that the combination of CIK/DC-CIK immunotherapy and cytotoxic chemotherapy: enhances the immune function of patients, alleviates the adverse effects of chemotherapy, and improves the overall response, disease control, and quality of life [272].…”
Section: Nk Cells In Solid Tumorsmentioning
confidence: 99%